2016
DOI: 10.1002/hed.24373
|View full text |Cite
|
Sign up to set email alerts
|

Validation of methodology for assessment of pulmonary function in patients who undergo total laryngectomy

Abstract: The methodology for the assessment of the pulmonary function by using the extratracheal proposed device is reliable, accurate, and reproducible. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2030-E2034, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…On the other hand, we observed that pulmonary functions measured by spirometry did not reflect the risk of ILD. Pulmonary functions are thoroughly assessed in patients who will undergo a laryngectomy, and thus our findings are not derived from the insufficiency of the pulmonary function tests …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, we observed that pulmonary functions measured by spirometry did not reflect the risk of ILD. Pulmonary functions are thoroughly assessed in patients who will undergo a laryngectomy, and thus our findings are not derived from the insufficiency of the pulmonary function tests …”
Section: Discussionmentioning
confidence: 99%
“…Several studies evaluated the reproducibility of different extratracheal devices, but detailed analysis in lung function is still lacking. In addition, systems used for this cause often were associated with technical problems, such as leakages, or were uncomfortable for patients . As a result, there is an unmet need for a standardized and simple method for routine use in order to perform reliable lung function tests in laryngectomized patients.…”
Section: Discussionmentioning
confidence: 99%